2022
DOI: 10.1038/s41467-022-35342-x
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic signaling mediates cortical early tagging and storage of remote memory

Abstract: The neocortical prefrontal memory engram generated during initial learning is critical for remote episodic memory storage, however, the nature of early cortical tagging remains unknown. Here we found that in mice, increased norepinephrine (NE) release from the locus coeruleus (LC) to the medial prefrontal cortex (mPFC) during contextual fear conditioning (CFC) was critical for engram tagging and remote memory storage, which was regulated by the ventrolateral periaqueductal grey. β-Blocker infusion, or knockout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Supporting this claim, β agonists induced anxiogenic effects in rodents ( Hecht et al, 2014 ). Further, β activation impairs fear extinction ( Atzori et al, 2016 ) and remote footshock-induced memory ( Fan et al, 2022 ), which may lead to a more dramatic and persistent anxiogenic response upon bulk activation. Though research surrounding specific β-AR subtype modulation in the PFC is sparse, a recent study demonstrated β2 optogenetic activation in the mPFC resulted anxiogenic responses in the OFT and EZM.…”
Section: Lc-ne System Modulates Pfc Neural Activitymentioning
confidence: 99%
“…Supporting this claim, β agonists induced anxiogenic effects in rodents ( Hecht et al, 2014 ). Further, β activation impairs fear extinction ( Atzori et al, 2016 ) and remote footshock-induced memory ( Fan et al, 2022 ), which may lead to a more dramatic and persistent anxiogenic response upon bulk activation. Though research surrounding specific β-AR subtype modulation in the PFC is sparse, a recent study demonstrated β2 optogenetic activation in the mPFC resulted anxiogenic responses in the OFT and EZM.…”
Section: Lc-ne System Modulates Pfc Neural Activitymentioning
confidence: 99%
“…Blocking NE neurotransmission impairs this ability and is not easily rescued with LC activation. Moreover, the expression of freezing representing a CFC memory was regulated by the LC-PAG pathway ( Fan et al, 2022 ). It will be interesting to see how future studies explore these other coerulear projections in terms of engram dynamics as well as examine the similarities and differences between LC neuromodulatory actions in these regions as compared to the hippocampus.…”
Section: Concluding Perspectives and Future Research Directionsmentioning
confidence: 99%
“…75 These sensors have also been instrumental in demonstrating the link between NA temporal dynamics and learning, 26,99 as well as NA and memory consolidation. 8,100 By imaging NA sensors in combination with optogenetics, researchers have begun to reveal the link between LC neuronal activity and NA release in target regions. 22,93,94,96,101 When combining these tools, it is critical to select optically compatible molecules, to avoid any interference between the excitation wavelengths of the opsin and the sensor.…”
Section: Monitoring the Release Of Noradrenaline With Lightmentioning
confidence: 99%
“…Using either fiber photometry or two-photon imaging, researchers have used these sensors to uncover the temporal dynamics of NA release associated with various behavioral states, such as sleep, 4 , 8 , 9 the default mode network, 97 arousal, 73 , 98 and the processing of aversive stimuli 75 . These sensors have also been instrumental in demonstrating the link between NA temporal dynamics and learning, 26 , 99 as well as NA and memory consolidation 8 , 100 …”
Section: Monitoring the Release Of Noradrenaline With Lightmentioning
confidence: 99%
See 1 more Smart Citation